A communicative grammar of english - Leech, Geoffrey (Longman, 2002)
A Communicative Grammar of English was first published in 1975, since then the book has established itself as a grammar innovative in approach, reliable in coverage, and clear in its explanations. It is now available in this fully revised and redesigned third edition to provide up-to-date and accessible help to teachers, advanced learners and undergraduates students of English. A completely new Workbook co-authored by ELT specialists Edward Woods and Rudy Coppieters will also accompany this edition. This edition is divided into three parts: Part One: A guide to the use of this book, this looks at the way English grammar varies in different types of English, for example 'formal' and 'informal', 'spoken' and 'written' Part Two: Grammar in use, the most important part, presents grammar through the eyes of the communicator and focuses on the uses of grammar rather than on grammatical structure Part Three: A-Z in English grammar provides an alphabetically arranged guide to English grammar